SPOP and FOXA1 mutations are associated with PSA recurrence in ERG wt tumors, and SPOP downregulation with ERG‐rearranged prostate cancer. Issue 10 (15th May 2019) - Hernández‐Llodrà, Silvia; Segalés, Laura; Safont, Ainara; Juanpere, Nuria; Lorenzo, Marta; Fumadó, Lluís; Rodríguez‐Vida, Alejo; Cecchini, Lluís; Bellmunt, Joaquim; Lloreta‐Trull, Josep
Abstract: Background: ERG fusion‐related prostate cancer (PrCa) is the most prevalent oncogenic driver subclass. SPOP, FOXA1, and IDH1 mutations are other three main oncogenic driver subclasses in non– ETS ‐fusion PrCa. ERG protein levels seem to be increased in SPOP ‐mutated cases, and different studies reported that SPOP mutations and ERG fusions are mutually exclusive. The aim of this study has been to analyze the alterations in non– ETS ‐oncogenic drivers in PrCa. Methods: SPOP, FOXA1, and IDH mutations were investigated by polymerase chain reaction (PCR) and Sanger direct sequencing. ERG, SPOP, and TMPRSS2‐ERG messenger RNA expression was assessed by quantitative real‐time PCR from complementary DNA, and the presence of the fusion was also analyzed by nonquantitative PCR. The clinical pathological features were retrieved from the charts of the 111 patients included in the study (MARBiobanc, Barcelona, Spain). Results: Loss of SPOP expression (25.2%) was associated with ERG overexpression ( P  = 0.0036). SPOP mutations were found in 5.4% cases, all with wild‐type (wt) ERG ( P  = 0.007). FOXA1 mutations were found in 8.2% cases, most of them ERG wt ( P  = 0.06). No IDH1 mutations were found. SPOP or FOXA1 mutations were found in 1.7% of ERG ‐rearranged, and 34.2% of non–ERG‐rearranged cases ( P <  0.0001). SPOP or FOXA1 alterations (mutations or expression loss) were significantly more common in GG5, while isolated ERG overexpression was more common in GG1 tumors ( P  = 0.042). SPOP ‐or FOXA1 ‐mutated cases were associated with a shorter time to prostate‐specific antigen (PSA) recurrence in the univariate ( P =  0.0009), and with the PSA recurrence risk in the multivariate ( P  = 0.023) analysis. Conclusions: In conclusion, SPOP and FOXA1 mutations may have prognostic value in ERG wt tumors. Interestingly, in absence of SPOP mutations, downregulation of this gene is a feature of many ERG‐ rearranged prostate tumors.